Association of CCL5 and CCR5 Gene Polymorphisms With Periodontitis in Taiwanese. Issue 11 (1st November 2014) - Shih, Yo‐Seng; Fu, Earl; Fu, Martin M.; Lin, Fu‐Gong; Chiu, Hsien‐Chung; Shen, E‐Chin; Chiang, Cheng‐Yang
Abstract : Background: It has been suggested that genetic factors may predispose individuals to periodontal diseases. The present case‐control study aims to test whether the −403 single nucleotide polymorphism of chemokine ligand 5 (CCL5‐403) and the 32‐bp deletion of CCR5 (CCR5Δ32) polymorphisms are associated with susceptibility to chronic and aggressive periodontitis. Methods: Taiwanese participants (N = 213) were grouped into control group (CG), generalized aggressive periodontitis (GAgP), or chronic periodontitis (CP) groups. DNA samples were obtained from peripheral blood. CCL5‐403, evaluated by polymerase chain reaction‐restriction fragment length polymorphism, and CCR5Δ32, evaluated by polymerase chain reaction, were compared among the three groups. Results: There was a significant association between type of periodontitis and having allele A or G in the CCL5‐403 polymorphism. GAgP patients were 3.7 times more likely than CP patients and 2.0 times more likely than CG patients to have allele A, instead of allele G, in CCL5‐403. GAgP patients were 3.1 times more likely than CG patients to have AG versus GG genotype. GAgP patients were also 5.0 and 19.8 times more likely than CP patients to have AG and AA genotypes, respectively, compared to GG. For the CCR5Δ32 polymorphism, no association was found between the type of periodontitis and having different genotype or allele distributions among GAgP, CP, or CG patients. Conclusion: The single nucleotide polymorphism of CCL5‐403 G substitution by A may play a role in AgP; however, the CCR5Δ32 polymorphism may not.